Confabulation: What is associated with its rise and fall? A study in brain injury. (February 2017) - Bajo, Ana; Fleminger, Simon; Metcalfe, Chris; Kopelman, Michael D.
Abstract: The aim of this study was to investigate cognitive and emotional factors associated with the presence and clinical course of confabulation. 24 confabulating participants were compared with 11 brain injured and 6 healthy controls on measures of temporal context confusions (TCC), mood state (elation, depression) and lack of insight. Measures of autobiographical memory and executive function were also available. Changes in confabulation and these other measures were monitored over 9 months in the confabulating group. We found that TCC were more common in confabulating patients than in healthy controls, and that the decline in these errors paralleled the recovery from confabulation. However, TCC were not specific to the presence of confabulation in brain injury; and their decline was not correlated with change in confabulation scores over 9 months. We found that elated mood and lack of insight discriminated between confabulating and non-confabulating patients, but these measures did not correlate with either the severity of confabulation or change in confabulation scores through time. What seems to have been most strongly associated with the severity of confabulation scores at 'baseline' and changes through time (over 9 months) were the severity of memory impairment (especially on autobiographical memory) and errors on executive tests (particularly in making cognitive estimates). Greater autobiographical memory and executive impairment were associated with more severe confabulation. The findings were consistent with the view that confabulation results from executive dysfunction where autobiographical memory is also impaired; and that it resolves as these impairments subside.